2017
DOI: 10.1209/0295-5075/120/40001
|View full text |Cite
|
Sign up to set email alerts
|

GUP parameter and black-hole temperature

Abstract: Motivated by a recent work of Scardigli, Lambiase and Vagenas (SLV), we derive the GUP parameter, i.e. α 0 , when the GUP has a linear and quadratic term in momentum. The value of the GUP parameter is obtained by conjecturing that the GUP-deformed black hole temperature of a Schwarzschild black hole and the modified Hawking temperature of a quantum-corrected Schwarzschild black hole are the same. The leading term in both cases is the standard Hawking temperature and since the corrections are considered as ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…A similar result has been recently recovered in Ref. [55], where, by conjecturing the equality between the GUP-deformed black hole temperature of a Schwarzschild black hole and the modified Hawking temperature of a quantum-corrected Schwarzschild black hole, it has been obtained a GUP parameter depending on the ratio m p /M .…”
Section: Discussionsupporting
confidence: 81%
“…A similar result has been recently recovered in Ref. [55], where, by conjecturing the equality between the GUP-deformed black hole temperature of a Schwarzschild black hole and the modified Hawking temperature of a quantum-corrected Schwarzschild black hole, it has been obtained a GUP parameter depending on the ratio m p /M .…”
Section: Discussionsupporting
confidence: 81%
“…Next, we argue that the deformed QRE metric would imply a quantum correction to Newton's law, similar to the one obtained from the tree diagrams of graviton exchange in the weak field limit [21,22]. It has already been shown that the GUP corrections have a thermal nature [19], and that both quadratic and linear-quadratic GUP deformations correspond to the tree-level correction to the Schwarzschild metric [19,20,23]. To explicitly show the above correspondence between QRE and GUP, we need to relate the two deformation parameters.…”
supporting
confidence: 61%
“…Following Ref. [70,71], for a line element parametrized as in Eq. (6), the associated horizon temperature can be written as…”
Section: Gup and Scale-dependent Bh Temperaturementioning
confidence: 99%